Pemanfaatan Biochar Sebagai Media Filtrasi dalam Pengolahan Air Tercemar Logam Berat: Kajian Efektivitas, Mekanisme Adsorpsi, dan Kelayakan Implementasi di Masyarakat - Suwarsono, Annysah Amalyah; Fitriani, Nurul Dwi; Yazid, M.; S'more, Josetionov; Prasetyo, Haris; Ardiatma, Dodit (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Water pollution by heavy metals such as lead (Pb), cadmium (Cd), and chromium (Cr) is a serious environmental problem, particularly in industrial areas such as Bekasi, West Java. Heavy metals are toxic, non-biodegradable, and bioaccumulate in food chains, posing serious risks to human health and ecosystems. This study aimed to evaluate the effectiveness of rice husk and coconut shell-based biochar as alternative filter media through a systematic literature review of scientific articles published between 2021 and 2026, indexed in Scopus, Web of Science, and Google Scholar. The results indicate that coconut shell biochar produced at a pyrolysis temperature of 550°C achieves a BET surface area of 387 m²/g and removal efficiencies of 93.8% for Pb(II), 88.5% for Cd(II), and 81.2% for Cr(VI). The adsorption mechanism is multimechanistic, involving ion exchange, surface complexation, precipitation, and physical adsorption, with kinetics best described by the pseudo-second-order model (R² ≥ 0.99). Feasibility analysis demonstrates that a household-scale biochar filter unit can be produced for IDR 149,000–300,000 and can treat 50–100 liters of water per day with a service life of 3–6 months. Iron-modified biochar innovations improve heavy metal removal efficiency by 25–45% compared to conventional biochar. This technology is deemed technically, economically, and environmentally feasible as an appropriate technology solution for water treatment in low-income communities